Role of Keratinocytes in the Development of Vitiligo - Lee, Ai-Young (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2012)
Vitiligo is an acquired depigmentary disorder of the skin that results from the loss of functioning epidermal melanocytes. Most studies on vitiligo have concentrated on the abnormality of melanocytes rather than the abnormality of keratinocytes; however, epidermal melanocytes form a functional and structural unit with neighboring keratinocytes. In fact, direct cell-to cell contact stimulates in vitro proliferation of melanocytes, and growth factors produced by adjacent keratinocytes regulate the proliferation and differentiation of melanocytes. The potential role of keratinocyte-derived cytokines has also been presented. We focused on the structural changes in vitiliginous keratinocytes, which may result in loss of melanocytes, to examine the pathomechanism of vitiligo. The results of a comparison between depigmented and normally pigmented epidermis in patients with vitiligo showed that the keratinocytes in the depigmented epidermis were more vulnerable to apoptosis. Impaired Phosphatidylinositol 3-kinase (PI3K)/serine/threonine protein kinase (Akt) activation followed by reduced nuclear factor-κB activation under increased tumor necrosis factor-α levels was demonstrated as a mechanism for keratinocyte apoptosis. The role of aquaporin 3 in keratinocyte apoptosis was addressed based on the relationship between the PI3K/AKT pathway and the E-cadherin-catenin complex. Apoptotic keratinocytes induced a lower expression of keratinocyte-derived factors, including stem cell factor, in depigmented epidermis, resulting in passive melanocyte death.